2018
DOI: 10.1038/s41598-018-23463-7
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and degree of territorial aggression differs among urban and rural great tits (Parus major)

Abstract: Animals in urban habitats face many novel selection pressures such as increased human population densities and human disturbance. This is predicted to favour bolder and more aggressive individuals together with greater flexibility in behaviour. Previous work has focussed primarily on studying these traits in captive birds and has shown increased aggression and reduced consistency between traits (behavioural syndromes) in birds from urban populations. However, personality (consistency within a behavioural trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 88 publications
(150 reference statements)
6
31
1
Order By: Relevance
“…Similarly, previous studies reported more variation in the expression of measured behavioural responses in urban individuals compared to rural ones (e.g. 22 , 84 , 101 ). For example, Lehrer et al 101 found increased variance of vigilance behaviour in woodchucks ( Marmota monax ) along the rural–urban gradient.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Similarly, previous studies reported more variation in the expression of measured behavioural responses in urban individuals compared to rural ones (e.g. 22 , 84 , 101 ). For example, Lehrer et al 101 found increased variance of vigilance behaviour in woodchucks ( Marmota monax ) along the rural–urban gradient.…”
Section: Discussionsupporting
confidence: 63%
“…Findings are consistent with previous literature on birds and larger mammals, suggesting an ubiquitous response to human-altered environments across taxa. Urbanisation may therefore act as a selective force driving the evolution of behavioural and phenotypic differences between urban and rural populations 22 . Cities provide a natural laboratory for understanding which role human activity plays in the reciprocal interactions between ecological and evolutionary processes, since the accelerated rates and increased magnitude of landscape-level changes mark them as hotspots of contemporary evolution 110,112 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotype-matching habitat choice has been suggested as an explanation for settlement patterns in relation to human disturbance in dunnocks, Prunella modularis (Holtmann et al 2017). Moreover, it has been found that urban great tits differ in consistent behavioural traits from their rural conspecifics (Hardman and Dalesman 2018). It might well be that nonrandom distributions of great tit phenotypes also occur at smaller spatial scales within cities, such that individuals that are less sensitive to nocturnal disturbance are more likely to settle in disturbed areas.…”
Section: Discussionmentioning
confidence: 99%